Comparación de la capacidad a flexión de la superestructura de un puente con tablero tipo losa de diferente sección transversal - Zaruma Pesantez, Cristhian Andrés (My University, 2022)
In this work, we will compare the bending capacity of the superstructure of a bridge with a solid slab type deck and a relieved slab type deck of 14 meters long, 8.55 meters wide and 0.48 meters thick, whose dimensions were taken from visits to local bridges such as the General Manuel Serrano Bridge, located over the Jubones River in the La Iberia sector of the El Guabo canton, which is composed of isostatic spans.For the development of the calculations, the method indicated by the AASTHO-LRFD 2014 American Association of State Highway Transportation Officials - Load, Resistance, Factor, Design, standard was used, which indicates the design limit states. The dimensions taken in the field were used to calculate and obtain the ultimate moments, then the calculation of the main steel was performed, obtaining a moment per capacity and thus making the demand/capacity relationship to bending in the two types of deck to be developed. Structural analysis software will be used to calculate the inertia of each type of deck, and then we will calculate the deformations produced in each case by gravity loads placed on the superstructure.
En el presente trabajo, se comparará la capacidad a flexión de la superestructura de un puente con tablero tipo losa maciza y tipo losa alivianada de 14 metros de longitud, 8.55 metros de anchos y un espesor de 0.48 metros cuyas dimensiones se tomaron de visitas a puentes de la localidad como lo es el Puente General Manuel Serrano, ubicado sobre el rio Jubones en el sector La Iberia del cantón El Guabo, que está compuesto por vanos isostáticos. Para el desarrollo de los cálculos se empleó el método que nos indica la norma AASTHO–LRFD 2014 .American Associatión of State Highway Transportation Officials - Load, Resisten, Factor, Desing, el cual nos indica los estados límites de diseño. Se partido de las dimensiones tomadas en campo para el calculo y obtención de los momentos últimos, luego se realizó el cálculo del acero principal obteniendo un momento por capacidad y de esa manera realizar la relación Demanda/capacidad a flexión en los dos tipos de tablero a desarrollar. Para el cálculo de las inercias de cada tipo de tablero se utilizará un software de análisis estructural, luego realizaremos el cálculo de las deformaciones producidas en cada caso por cargas gravitacionales dispuestas sobre la superestructura.
Keywords: SUPERESTRUCTURA; FLEXION; NORMA AASTHO–LRFD; DEFORMACION